Computer-Aided Design of Electro-Optical Assemblies - Zeitler, Jochen; Franke, Jörg (Springer International Publishing, 2022)
The integration of the different engineering disciplines in an integrated development procedure is the core of this chapter. For this purpose, the physical and technological principles of optical technologies must be considered. Product development methods of technical systems are a related field, since up to now, especially for 3D-Opto-MID, no adequate methodology exists. Analogies to mechatronic systems and their sub-processes do exist, but these must be evaluated and expanded with regard to the new optomechatronic components. A separate procedure that differs from conventional development methods is just as important as the challenges that must be placed on modeling systems, the designer and the production of the 3D-Opto-MID. From these defined requirements, it was possible to derive a concept for a 3D optomechatronics CAD software (OMCAD) which contains the essential steps for creating these products.
CRIS-Team Scopus Importer:2024-12-16